2020
DOI: 10.4162/nrp.2020.14.2.95
|View full text |Cite
|
Sign up to set email alerts
|

Enzymes involved in folate metabolism and its implication for cancer treatment

Abstract: BACKGROUND/OBJECTIVES: Folate plays a critical role in DNA synthesis and methylation. Intracellular folate homeostasis is maintained by the enzymes folylpolyglutamate synthase (FPGS) and γ-glutamyl hydrolase (GGH). FPGS adds glutamate residues to folate upon its entry into the cell through a process known as polyglutamylation to enhance folate retention in the cell and to maintain a steady supply of utilizable folate derivatives for folate-dependent enzyme reactions. Thereafter, GGH catalyzes the hydrolysis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 71 publications
0
20
0
Order By: Relevance
“…A previous study [ 20 ], using a representative sample of the Korean population from the Korean National Health and Nutrition Examination Survey (KNHANES), included multivariable linear regressions to derive the prediction equations for lean body mass index (LBMI), body fat mass index (BFMI), and appendicular skeletal mass index (ASMI). The following variables were used to derive the prediction equations: LBM, ASM, and BFM from whole-body dual-energy X-ray absorptiometry as dependent variables; and age, anthropometric measurements (height, body weight, and WC), blood test (serum creatinine levels), health-related behaviors (physical activity level, smoking status, and alcohol intake) as independent variables that can be related to factors that affect the body composition.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study [ 20 ], using a representative sample of the Korean population from the Korean National Health and Nutrition Examination Survey (KNHANES), included multivariable linear regressions to derive the prediction equations for lean body mass index (LBMI), body fat mass index (BFMI), and appendicular skeletal mass index (ASMI). The following variables were used to derive the prediction equations: LBM, ASM, and BFM from whole-body dual-energy X-ray absorptiometry as dependent variables; and age, anthropometric measurements (height, body weight, and WC), blood test (serum creatinine levels), health-related behaviors (physical activity level, smoking status, and alcohol intake) as independent variables that can be related to factors that affect the body composition.…”
Section: Methodsmentioning
confidence: 99%
“…The ICCs were all >0.9. Each of the prediction equations showed a high predictive power for each body composition [ 20 ] (LBMI, ASMI, and BFMI) and a low bias in the Bland–Altman plot, with good agreement between the actual measured and predicted values estimated by the suggested prediction equation when applied in large-scale population studies. In this study, each participant’s LBMI (kg/m 2 ), BFMI (kg/m 2 ), and ASMI (kg/m 2 ) were calculated using the prediction equations presented in the Supplementary Data .…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the relative expression status of key enzymes involved in folate metabolism is worthy of study in gynecological tumors. GGH is a lysosomal enzyme that catalyzes the formation of monoglutamyl folate, which in turn influences DNA synthesis ( Kim, 2020 ). It is highly expressed in the human kidneys, liver, fetal tissue, and placenta, whereas its expression in the spleen, lungs, small intestine, and peripheral blood leukocytes is relatively low ( Yin et al, 2003 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that activation of MAPK, KRAS, or STAT3 pathways alter cell proliferation, apoptosis, and other biological behaviors that influence the occurrence and progression of UCEC ( Fathi et al, 2018 ; Li et al, 2018 ; Sideris et al, 2019 ). It was also reported that changes in the GGH-dependent regulation of folate concentration affect intracellular mitochondrial metabolism, gene expression, DNA methylation, and DNA repair efficiency ( Kim et al, 2015 ; Kim, 2020 ). Higher expression of GGH can accelerate the conversion of polyglutamyl folate to the monoglutamyl form and reduce total folate levels.…”
Section: Discussionmentioning
confidence: 99%
“…19,20 Increased folate cycle-driven metabolism is important for maintaining the malignant phenotypes of cancer cells. 21,22 Methylenetetrahydrofolate dehydrogenase1 like (MTHFD1L) is a mitochondrial enzyme of the folate cycle that catalyzes the reaction of 10-formyltetrahydrofolate to formate and tetrahydrofolate (THF). Formate then enters the cytoplasmic compartment and serves as an important source of one-carbon donor molecules.…”
Section: Introductionmentioning
confidence: 99%